2022
DOI: 10.7759/cureus.29893
|View full text |Cite
|
Sign up to set email alerts
|

Massage Therapy to Control Anxiety Before Extraction of an Impacted Tooth

Abstract: Anxiety creates a stressful situation for the dentist as well as the patient. This article describes a simple technique to manage anxiety using an eye massager. The audio and visual distraction technique helps the patient relax and complete the procedure. This article also stresses some basic skills like good communication skills and establishing mutually trustworthy dentist-patient relationships to enhance patient satisfaction during treatment. Managing anxiety during dental visits will help improve oral heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…allowing the patient to carry out the treatment with ease. It makes short dental procedures like making impressions, injecting local anesthesia [8], or taking intraoral radiographs more comfortable for the patient. This technique is valuable for patients with mild gag reflexes, as it helps them remain calm and relaxed during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…allowing the patient to carry out the treatment with ease. It makes short dental procedures like making impressions, injecting local anesthesia [8], or taking intraoral radiographs more comfortable for the patient. This technique is valuable for patients with mild gag reflexes, as it helps them remain calm and relaxed during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Research has thus shown that the level of DA was the highest in patients who were indicated for oral surgery, compared to patients who needed conservative or endodontic treatment on their teeth 19 . Causing anxiety through interventions in the oral cavity is a universal phenomenon, which could be intensified by smell, sound, and light, as well as previous experience 20 . A large number of patients who faced an anxious experience in the dental office considered it one of the most unpleasant experiences in their life 21 .…”
Section: Discussionmentioning
confidence: 99%